American Indian trickster tales - Erdoes, Richard; Ortiz, Alfonso, 1939- (New York : Viking, 1998)
Contains over one hundred tales drawn from the Native American traditions of fifty-five North American tribes, each featuring the ever-changing character of the trickster.
Includes bibliographical references (p. [285]-293) and index.
Booklist
Multicultural Review
Publisher's Weekly
Young Adult.
Young Adult
Keywords: Indians of North America -- Folklore; Tales -- North America; Trickster -- Folklore; Folklore; Native Americans -- Folklore; Trickster -- Folklore